Cascade extraction of proteins and feruloylated arabinoxylans from wheat bran. (15th December 2020) - Yilmaz-Turan, Secil; Jiménez-Quero, Amparo; Moriana, Rosana; Arte, Elisa; Katina, Kati; Vilaplana, Francisco
Highlights: Proteins and feruloylated arabinoxylans were sequentially extracted from wheat bran. The protein isolation step enhanced subsequent arabinoxylan extraction. High temperature enhanced arabinoxylan extraction at the expense of hydrolysis. The feruloylated arabinoxylans displayed significant antioxidant properties. Abstract: A cascade process for the sequential recovery of proteins and feruloylated arabinoxylan from wheat bran is proposed, involving a protein isolation step, enzymatic destarching and subcritical water extraction. The protein isolation step combining lactic acid fermentation and cold alkaline extraction reduced the recalcitrance of wheat bran, thus improving the total yields of the subsequent subcritical water extraction. The time evolution of subcritical water extraction of feruloylated arabinoxylan was compared at two temperatures (160 °C and 180 °C). Longer residence times enhanced the purity of target feruloylated arabinoxylans, whereas higher temperatures resulted in faster extraction at the expense of significant molar mass reduction. The radical scavenging activity of the extracted feruloylated arabinoxylans was preserved after the initial protein isolation step. This study opens new possibilities for the cascade valorization of wheat bran into enriched protein and non-starch polysaccharide fractions, which show potential to be used as functional food ingredients.